Impact of the preoperative clinical N stage on the prognosis of patients with colon cancer. (28th October 2022) - Takaki, Wataru; Arita, Tomohiro; Kuriu, Yoshiaki; Shimizu, Hiroki; Kiuchi, Jun; Ohashi, Takuma; Yamamoto, Yusuke; Konishi, Hirotaka; Morimura, Ryo; Shiozaki, Atsushi; Ikoma, Hisashi; Kubota, Takeshi; et al.
Abstract: Aim: Although preoperative clinical staging (cStage) is performed for most cancer patients, limited information is currently available on the relationship with postoperative prognosis. We herein investigated the relationship between cStage and prognosis of colon cancer (CC) patients, particularly focusing on the presence or absence of clinical lymph node (LN) metastasis. Method: This was a retrospective study on 840 consecutive patients with colon adenocarcinoma who underwent radical resection at our institution between January 2007 and December 2018. A Kaplan–Meier curve was used to analyse the prognosis of two groups: cN(+)pN(−); a group preoperatively diagnosed with clinical LN metastasis positive, but with no pathological LN metastasis postoperatively, and cN(−)pN(−); a group without clinical and pathological LN metastasis. We also investigated whether a clinical diagnosis is a more accurate prognostic factor than other clinical factors. Results: Among pN(−) cases, the 5‐year recurrence‐free survival rate was significantly lower in preoperatively diagnosed cN(+) cases than in cN(−) cases (79.4% vs. 95.6%, 3.04 years vs. 3.85 years, p < 0.01). In a multivariate analysis of various preoperative clinical factors in pStage II cases, including high risk factors for pStage II CC, cN(+) was identified as an independent prognostic factor (hazard ratio: 2.06, 95% CI: 1.02–4.27, p = 0.04). Conclusion: Preoperatively over‐staged cN cases had a poorer prognosis than cases without over‐staging, indicating its potential as a prognostic factor. In addition to already known high risk factors in pStage II cases, the preoperative cStage may be an indication for adjuvant chemotherapy.